THE EFFECT OF FINANCIAL DISTRESS, COMPANY SIZE, AND PREVIOUS YEAR’S AUDIT OPINION ON GOING CONCERN AUDIT OPINION OF TEXTILE AND GARMENT SUB SECTOR COMPANIES - setyawati, Dyah Mieta (Archives of Business Research, 2021)
ABSTRACT Going concern audit opinion is an audit opinion that given by the auditors when they have doubts about the company's ability to sustain its business. The purpose of this study is to determine the influence of financial distress, company size, and the previous year’s audit opinion on going concern audit opinion. The data used is secondary data of textile and garment sub-sector companies listed on the Indonesia Stock Exchange. The sampling method used was purposive sampling method. The samples used were 15 companies in the textile and garment sub-sector with the 2016-2019 research period. The analysis technique used was the modified Altman method and logistic regression analysis with the help of SPSS version 26. The results of the analysis show that financial distress and the previous year's audit opinion have an effect on going-concern audit opinion. Meanwhile, company size has no effect on going concern audit opinion. And the overall results show that financial distress, company size, and previous year's affect on going concern audit opinion.